Compliance of Outpatient Prescriptions with National Pharmaceutical Standards: A Cross-Sectional Study at Military Hospital in Jakarta - Sondang Khairani; Wanda Ditan Arvandi; Safira Nafisa; Desi Nadya Aulena (Indonesian Journal of Administrative and Clinical Pharmacy, 2025)
Hospital pharmaceutical services play a crucial role in ensuring the quality of patient care, particularly through prescription screening, which includes administrative and pharmaceutical aspects. This study aimed to evaluate the completeness of BPJS outpatient prescriptions at one of military hospital in Jakartabased on national standards. A retrospective descriptive study was conducted on 367 prescriptions from February to April 2023, selected using simple random sampling. Data were analyzed using descriptive statistics. The results showed full completeness (100%) for patient name, medical record number, diagnosis, physician name, and prescription date in the administrative section. However, gender (6.3%) and physician license number (2.7%) were often missing. For the pharmaceutical section, all indicators were complete except for strength (98.9%), dosage form (99.7%), duration (99.7%), and stability (0%). In conclusion, the pharmaceutical elements of prescriptions mostly complied with national standards, but administrative completeness remains a concern and needs system-level improvements.